2019
DOI: 10.1016/j.est.2018.11.032
|View full text |Cite
|
Sign up to set email alerts
|

The effect of supercapacitors in a tidal current conversion system using a torque pulsation mitigation strategy

Abstract: The research presented in this paper investigates the effect of connecting supercapacitors at the DC link of a hypothetical 1.5MW three-bladed variable-pitch horizontal-axis tidal current turbine that uses a torque pulsation mitigation strategy. Torque pulsations are classified into fatigue torque and ultimate or peak torque. Both can lead to premature components failure or system overdesign and costly maintenance. Research has suggested that torque pulsations can be mitigated by using a novel control strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…It is noted that tidal power is a predictable energy resource, whose accuracy has been within 98% for decades. This predictability allows tidal power generation to be successfully integrated into electrical grids [4][5][6][7][8]. The typical behaviour of the power system has changed because of the increasing use of renewable energy sources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noted that tidal power is a predictable energy resource, whose accuracy has been within 98% for decades. This predictability allows tidal power generation to be successfully integrated into electrical grids [4][5][6][7][8]. The typical behaviour of the power system has changed because of the increasing use of renewable energy sources.…”
Section: Introductionmentioning
confidence: 99%
“…However, tidal energy generation comes with many challenges, and its integration into the grid presents numerous operational and control difficulties that limit the grids' ability to run steadily and dependably. Therefore, it is important to maintain the stability of voltage and frequency in the power network by ensuring that harmonic distortions are kept as low as possible [7,10]. In power converters with a rectifier input stage, LCL filters are specially designed to cut down on harmonic current absorption (frequency converters for UPS, motors, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…In the literature it is possible to find charging/discharging systems implemented with different bidirectional converters like Boost [6,7], Buck-Boost [8,9], Cuk [10,11], Zeta/Sepic [12], Sepic/Zeta [13,14], or flyback [15]. The Boost converter has some advantages like its simplicity, reduced number of components, and simple control system, regarding Buck-Boost, Cuk, Zeta/Sepic, and Sepic/Zeta.…”
Section: Introductionmentioning
confidence: 99%
“…The study demonstrated that cascaded ADRC approach slightly improved a tidal turbine system production during swell wave disturbance periods in contrast with the conventional PI controllers. An investigation about the mitigation of undesired torque pulsations by changing the generator speed was presented by Sousounis et al [4]. The authors propose that the DC link voltage spikes, the electrical components stress increment, and the hazard to grid connection produced by increasing the variation of the generator rotational speed can be overcome by installing a supercapacitor module at the DC link.…”
Section: Introductionmentioning
confidence: 99%